DETERMINATION OF THE MAIN VARIABLES THAT DETERMINE THE INDUSTRIAL LOCATION IN THE PARTY OF LA MATANZA, BUENOS AIRES, ARGENTINA, THROUGH PROSPECTIVE ANALYSIS (Journal of Industrial and Mechanical Engineering, 2019)
The metropolitan area of Buenos Aires, owns 36% of the population and represents over 60% of industrial GDP Argentina, in just under 4% of the territory of the Province of Buenos Aires.In this context, the county of La Matanza, the most populous county and the largest contribution to provincial industrial GDP (22%), is characterized by having a very diverse set of industries, mainly SMEs; however sprawl of industrial activities in number and variety, also multiplied the creation of formal and informal institutions without rational location criteria, which are now a serious problem for industrial urban planning.This paper attempts to define a model that defines the main variables that determine industrial location in the district, serving as input for future policy and industrial relocation filing for the district.
Keywords: Location; Planning; Industry; La Matanza